Children’s magazines of Belarus in the pre-revolutionary period: typological features - Kharytonоva, Sviеtlana V. (Journal of the Belarusian State University. Journalism, 2020)
The article defines the main typological features of the first periodicals published on the territory of Belarus before the October revolution of 1917 for children’s readership. The author identifies changes in the socio-cultural and political contexts of the life of Belarusians in the pre-revolutionary Russian Empire and describes the conditions for the birth of national journalism for children. For the first time on the basis of studying the materials of the national archive and bibliographic catalogues of the national press of the late 19th – early 20th century, the author found that the history of Belarusian periodicals for children’s audience begins in 1905 with the release of the first monthly Russian-language illustrated magazine for children 8–14 years «Zorka». The article shows the results of the analysis of ideas and contents of specific journals «Zorka» and «Lucynka», specifics of the structural organisation of materials and art, and technical design of publications. The scientific novelty of the article consists in identifying new aspects of the study of the first Belarusian magazines for children, determining the main type-forming features of publications in accordance with the age category of the readership, the ideological content and design characteristics.
Keywords: periodicals for children; children’s magazines; typological features; content structure